Comparison of Evaluation and Selection of SmartPhones Recommended AHP, Weight Sum Model, and Weight Product - Akmaludin, Akmaludin; Sihombing , Erene Gernaria; Dewi, Linda Sari; Rinawati , Rinawati; Arisawati , Ester (Politeknik Ganesha Medan, 2022)
Advances in SmartPhone technology in the current era, make many users have more and more considerations to have a SmartPhone because there are many criteria that must be compared. The purpose of this paper is to give careful consideration for every user to have an optimal SmartPhone. Problems that are felt by many users as users find it difficult to make choices for electronic goods in the form of this SmartPhone. Thus, a number of methods are needed that are able to give careful and intelligent consideration to the user in order to obtain the acquisition of the electronic goods in the form of the SmartPhone. In short, the method that can be used to evaluate and select SmartPhones is the Analytic Hierarchical Process (AHP) which functions as a weight determination, while the Weight Sum Model (WSM) and Weight Product (WP) act as a ranking system. This method will be used to provide an optimal comparison value for SmartPhone products with decisions that can be seen based on the priority of the WSM vector and the WP vector, then based on the average of the two methods provide decision support results. The first position is Xiaomi Mi Max with a weight of 175 and followed sequentially onwards by Asus Zenfone Max ZC550KL (174), Samsung Galaxy J7 Prime (124), Lenovo Vibe Shot (117), Asus Zenfone 2 ZE551ML (113), Xiaomi Mi 4C (108 ), Lenovo Vibe K5 Plus (101), and finally the Samsung Galaxy A3 (89). Thus the combination method between the AHP, WSM and WP methods can provide the best solution with optimal results for decision-making support for comparison evaluation and selection in the form of a SmartPhone with optimal results.